2019
DOI: 10.1108/idd-06-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the benefits and challenges of learning analytics in higher education institutions: a systematic literature review

Abstract: Purpose The potential capabilities and benefits that learning analytics can provide are not fully utilized. A current stream of research suggests that learning analytics has more to offer for continuous improvement of higher education institutions. This study aims to explore the opportunities that data analytics stand to offer higher education and the challenges that plays down its role, adoption and usage in different areas of higher education institutions. Design/methodology/approach This study adopts a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 44 publications
1
20
0
5
Order By: Relevance
“…However, revealing such factors through the self-reported surveys from students may be difficult, as these surveys may not consider contextual factors in a detailed manner. This argument concurs with that of Alfy, Gómez, and Dani (2018) that learning analytics is context specific. This result shows that a blended data approach to studying the online behavior of students is feasible and beneficial.…”
Section: Discussionsupporting
confidence: 87%
“…However, revealing such factors through the self-reported surveys from students may be difficult, as these surveys may not consider contextual factors in a detailed manner. This argument concurs with that of Alfy, Gómez, and Dani (2018) that learning analytics is context specific. This result shows that a blended data approach to studying the online behavior of students is feasible and beneficial.…”
Section: Discussionsupporting
confidence: 87%
“…Their efforts proved that the social media usage has negative impact on academic activities (Giunchiglia et al, 2018). There are some pieces of evidence which indicates that higher education institutes which are interested in revealing information about students who are excessively involved in such networks (Fogel and Nehmad, 2009;El Alfy et al, 2019). For instance, "Thoughts on Facebook" published by the University of Cornel was aimed at informing students about responsible and accountable use of online social networking (Pempek et al, 2009).…”
Section: Background Of the Studymentioning
confidence: 99%
“…The works that investigated the benefits and challenges in LA in general were Avella et al (2016), Viberg et al (2018), Banihashem et al (2018), Alfy et al (2019); and related to LA policies was Tsai and Gasevic (2017). Avella et al (2016) revealed that several works on LA used data mining to predict, cluster and discover student models and emphasized the separation of data from human judgment to analyze data, and that these benefited course offerings, curriculum development and students learning outcomes.…”
Section: Previous Literature Review On Learning Analyticsmentioning
confidence: 99%
“…As benefits, the authors pointed out that LA could increase students engagement, improve learning outcomes, identify academically at-risk students, and provide real-time feedback and personalization of learning. Some of the benefits presented by Alfy et al (2019) were monitoring and predicting students' performance and helping academically at-risk students to succeed. Among the challenges identified was concerns about ethical use of data and data security.…”
Section: Previous Literature Review On Learning Analyticsmentioning
confidence: 99%